IMPLEMENTASI PROGRAM BANTUAN BAGI PELAKU USAHA MIKRO DI KECAMATAN GUBENG KOTA SURABAYA - Moch Rozzaq; Agus Widiyarta (Journal Publicuho, 2021)
In order to reduce the impact of the sustainability of MSMEs due to the Covid-19 pandemic, the government issued a BPUM (Assistance for Micro Business Players) policy. This policy is stated in the Regulation of the Minister of Cooperatives, Small and Medium Enterprises of the Republic of Indonesia number 6 of 2020 concerning BPUM and BPUM Implementation Guidelines number 98 of 2020. The purpose of this research is to determine the implementation of BPUM in the Gubeng District of Surabaya City. The theory used in this research is the implementation model theory by Edward III. The type of research used is descriptive qualitative. The results of this study indicate that: (1) Communication has been implemented even though the socialization has not been carried out massively; (2) Resources are well implemented; (3) The disposition has been implemented even though the employee response is not optimal; (4) The Bureaucratic Structure has been implemented in accordance with the Standard Operating Procedures (SOP) applicable to BPUM.